The adoption of electronic payment system among small medium enterprises (SMEs) in Malaysia / Nuryusmawati Mohd Yusof … [et al.] - Mohd Yusof, Nuryusmawati; Che Mohd Hariri, Mohd Shamim; Mohamed Taheer, Ahmad Shazeer; Syed Omar, Syed Ashrene (Faculty of Business and Management and UiTM Press, 2018)
This study aimed to investigate factors that significantly affect the adoption of electronic payment system (EPS) by local small and medium enterprise (SMEs) in Malaysia. Referring to the Central Bank of Malaysia’s report, it has stated that this country would achieve higher economic growth and higher competitiveness by fully migrating from paper-based payment system to electronic payment because the latter provide opportunities to enhance productivity level and lower cost of doing business. These four factors were simplicity, security/privacy, organization culture and top management support and how these factors may have impact on the adoption rate of electronic payment system. The population of this study was all the SMEs that are listed in SME Corporation Bhd, concentrated at all major cities in Malaysia. Proportionate sample was targeted from the company listings from SME Corp. Survey method was adopted in this study to achieve its objectives. A Likert five- point scale questionnaire was developed to collect the required data after reviewing some previous studies that related to the subject of the study. This study revealed that top management support and organizational culture have the strongest impact among the other independent variables on the adoption of EPS by SMEs in Malaysia. For future research, it is suggested that this research can be targeted according to state individually or by industry for better understanding on the adoption of EPS.